Living Qur’an as New Market Trends of Islamic Education in Indonesia - Shinta Nurani; Luthfi Maulana; Eni Purwati (Hayula: Indonesian Journal of Multidisciplinary Islamic Studies, 2022)
This research reviewed living Al-Qur’an as phenomenon and trend in learning Islamic Education in Indonesia. The causing factor is such as the moral panic of parents about modern-contemporary life. Many parents encourage their children to practice the Al-Qur'an, with the hope that the children will be more careful and fortify themselves from a free life. The panicked moral attitude of these parents is used by Islamic educational institutions as a market to gain capital gains, such as establishing an educational house/center based on living Qur'an learning. Several educational institutions also offer the concept of Islamic Boarding School, Tahfidz Center, and compete to use the Al-Qur'an as their product brand. This literature research used a social phenomenological science approach with the living Quran theory. This research found that 1) the trend of living Qur'an education in Islamic learning in Indonesian Islamic educational institutions was as a social impact of the spread of moral panic, 2) moral panic among parents of students became a new business field for managers of Islamic religious education institutions. 3) Al-Qur’an is a product that has its own market share, and 4) the phenomenon of living al-Quran was as a trend of Islamic education methods in Indonesia.